2014
DOI: 10.1097/01.ogx.0000456348.32099.6d
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use in Pregnancy and the Risk for Cardiac Defects

Abstract: Background-There is controversy regarding whether the use of selective serotonin reuptake inhibitors (SSRIs) and other antidepressants in pregnancy is associated with increased risks for congenital cardiac defects. In particular, concerns exist about a possible association between paroxetine and right ventricular outflow tract obstruction (RVOTO), and between sertraline and ventricular septal defects (VSD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…We created 100 propensity score strata of equal width, removed strata that did not contain at least 1 treated woman and 1 untreated woman because they are uninformative, and stratified the outcome models by these propensity score strata. 25 The high-dimensional propensity score algorithm evaluates thousands of inpatient and outpatient diagnoses, procedures, and pharmacy claims and prioritizes those covariates that may act as proxies for unmeasured confounders. These empirically identified confounders (n = 200) were combined with the investigator-specified covariates listed above in a propensity score model to improve confounding adjustment.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…We created 100 propensity score strata of equal width, removed strata that did not contain at least 1 treated woman and 1 untreated woman because they are uninformative, and stratified the outcome models by these propensity score strata. 25 The high-dimensional propensity score algorithm evaluates thousands of inpatient and outpatient diagnoses, procedures, and pharmacy claims and prioritizes those covariates that may act as proxies for unmeasured confounders. These empirically identified confounders (n = 200) were combined with the investigator-specified covariates listed above in a propensity score model to improve confounding adjustment.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…In 2005, the Food and Drug Administration made an advisory warning stating that there was an increased risk of cardiac malformations with the use of paroxetine (13). This was found for doses >25 mg daily (13), and there was no evidence for other SSRIs (14). Another concern is the potential for negative developmental effects in the offspring.…”
Section: Risks Of Ssrismentioning
confidence: 99%
“…20 At the same time, sertraline, while not reclassified, had also been associated with an increased risk for ventricular septal defects. 20 A follow-up nationwide cohort study of 949,504 pregnant Medicaid recipients from 2000 to 2007 showed a relative risk of any cardiac defect of 1.25 (95% confidence interval [CI], 1.13-1.38) in an unadjusted analysis of women using an SSRI in the first trimester. However, when adjusted for patients with only a depression diagnosis to control for confounding comorbid conditions, the relative risk was 1.12 (95% CI, 1.00-1.26).…”
Section: Antidepressantsmentioning
confidence: 99%
“…18,20,21 United States prevalence rates of SSRI use in pregnancy range from 8% to 13%. 8,20 Since up to 50% of pregnancies are unplanned, it is important for patients and health-care providers to be familiar with the impact of fetal exposure to SSRIs when prescribing these medications to women of reproductive age. While SSRIs are the mainstay of therapy and generally considered to be safe for use in pregnancy, there are some risks that must be considered.…”
Section: Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation